Evaluating Management Supports to the Internal Audit Function in Kenema District Council, Sierra Leone - Sualiho Sheriff; Mohamed Paul Ngegba (New Innovations in Economics, Business and Management Vol. 8, 2022)
Lack of management support and independence greatly hinders internal audit function operations’ effectiveness and efficiency. The purpose of this study was to look into the efficiency of management support for the internal audit function in the Kenema District Council in Eastern Sierra Leone. All officers of the Kenema District Council were included in the study. The internal audit procedure was previewed for 13 council officers using a simple random sample technique. From December 13th to December 20th, 2020, the 13 officers were given a pre-tested validated questionnaire with a reliability of 0.765. The majority of respondents said the council creates policy (92.3%), monitors and assesses (76.2%), and accepts audit materials (84.6%). In addition, (53.8%) of respondents strongly believe there is a link between management support and the efficacy of the internal audit function. Finally, the Kenema District Council administration ports the internal audit function in various ways. Some managerial support is insufficient, while others are adequate.